Seroepidemiology of Human Bocavirus Defined Using Recombinant Virus-Like Particles - Kahn, Jeffrey S.; Kesebir, Deniz; Cotmore, Susan F.; D'Abramo, Anthony; Cosby, Christi; Weibel, Carla; Tattersall, Peter (The Journal of Infectious Diseases, 2008)
Background. Human bocavirus (HBoV) is a newly identified human parvovirus for which seroepidemiology and antigenic properties remain undefined. Methods. The HBoV VP2 gene, expressed from a baculovirus vector, produced virus-like particles (VLPs), which were used to raise rabbit anti-HBoV antisera and to develop an enzyme-linked immunosorbent assay (ELISA). The VLP-based ELISA was used to screen for HBoV-specific immunoglobulinGantibodies in a convenience sample of 270 serum specimens, mostly from children, obtained at Yale–New Haven Hospital; 208 specimens were also screened for erythrovirus B19–specific antibodies by a B19 VLP–based ELISA. Results. Immunofluorescence and ELISA showed that human parvoviruses HBoV and B19 are antigenically distinct. By the HBoV VLP–based ELISA, 91.8% and 63.6% of serum specimens from infants in the first and second months of life, respectively, were found to be seropositive, as were 45.4% from 3-month-old infants and 25.0% from 4-month-old infants. The percentages of HBoV-seropositive children increased to 40.7%–60.0% for children 5l–47 months of age and to >85% for individuals ⩾48 months old. However, the overall percentage of B19-seropositive individuals was <40.5% for all age groups screened. Conclusions. HBoV infection is common during childhood, but a minority of children and young adults screened have evidence of B19 infection.